Securing IoT-Based Heating Control Systems in Critical Infrastructure: Challenes and Solutions - Boldizsár Bednárik; László Gogolák (Analecta)
The integration of smart technology into heating systems has led to increased efficiency and remote management capabilities. However, these advancements also introduce security vulnerabilities, especially in critical infrastructure. This paper explores the development of an IoT-based heating control system utilizing MQTT, ESP8266 microcontrollers, and Node-RED for centralized management. The study examines system design, identifies potential security threats, and proposes strategies to mitigate risks. Additionally, real-world case studies illustrate how cybersecurity weaknesses have impacted similar IoT applications in critical infrastructure, reinforcing the importance of implementing robust security measures.